ENERGY AUDIT AT CEBU INSTITUTE OF TECHNOLOGY, CEBU CITY TOWARDS AN ENERGY SAVING PROGRAM - Duaso, Cornelio G. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 15 No. 1, 2012, 2012)
This study sought to identify and analyze energy saving opportunities, analyze existing policies or programs, analyze existing practices through energy audit at the Cebu Institute of Technology, Cebu City as basis for saving energy of the institution. It utilized the descriptive method of research with a researcher-made questionnaire as the main instrument for data collection. Interviews and actual physical survey of all physical facilities of the school are also conducted. The monthly energy consumption of the total connected load at Cebu Institute Technology per building as reflected in electric bills were higher than the calculated data based on survey and perceptions of administrative personnel and working students. The causes of high electrical consumption per building of Cebu Institute of Technology were found out that the major consuming facility were continuously “switched- on” and poor monitoring on the electrical and mechanical devices that consumed electricity.